2012
DOI: 10.1109/lcomm.2011.111011.111898
|View full text |Cite
|
Sign up to set email alerts
|

Network-Based Distributed Mobility Control in Localized Mobile LISP Networks

Abstract: In Locator-Identifier Separation Protocol (LISP), the existing mobility control scheme is based on a centralized approach, in which the Map Server is used as a mobility anchor. However, such a centralized scheme has some limitations, including traffic overhead at central server, service degradation by a single point of failure, and larger handover delay. In this Letter, we propose a network-based distributed mobility control in localized mobile LISP networks. From numerical analysis, it is shown that the propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 3 publications
0
20
0
Order By: Relevance
“…For numerical results, the parameter values of T R−R , α, and β are set to 1, 3, and 2, respectively, based on [10]. Figure 4 shows the location update cost under different numbers of ARs.…”
Section: Numerical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For numerical results, the parameter values of T R−R , α, and β are set to 1, 3, and 2, respectively, based on [10]. Figure 4 shows the location update cost under different numbers of ARs.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…Centralized mobility management (CMM) employs only one MA and thus the MA can be a single point of failure and bottleneck. On the contrary, several MAs are deployed in distributed mobility management (DMM) and thus an additional mechanism is needed to find [10]. However, to the best of our knowledge, no works on comparative study among these mobility management schemes have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…However, these proposals still had some constraints such as the requirements of central server for mapping ID and LOC, tunneling for sending packets, or host modification [1,2,3,4,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…A larger number of papers have been presented to cope with problems in handover. Some popular problems include the handover delay [13][14][15][16], the ping-pong effect, the handover procedure in heterogeneous networks [17][18][19][20], and the handover failure rate [21][22][23][24]. However, as far as we know, there are not many papers studying link switching in VLC networks.…”
Section: Introductionmentioning
confidence: 99%